The analysis of Sap Water Yield and Palm Sugar (Arenga pinnata Merr.) Quality in Tasikmalaya District - Dedi Natawijaya; Suhartono Suhartono; Undang Undang (Balai Litbang Teknologi Agroforestry, Ciamis, 2018)
Development of high quality palm tree is needed for fulfilling the raw material of palm sugar and other products based on palm tree. This study aims to analyze the sap water yield and palm sugar quality in Tasikmalaya District. The method used in this study was survey and direct measurement of water content, pH, colour, texture, smell, taste, and performance. The geographical indication approach was used to determine the location of the study. The result showed that the average of sap water for palm sugar was 14.13% or 1 kg palm sugar equivalent to 7 litre of sap water, meanwhile 1 kg palm sugar powder equivalent to 7.6 litre of sap water (13.07%). The water content of palm sugar and palm sugar powder were 3.5% and 2.2% respectively.